Chemical Compositions, FTIR and Larvicidal Activity of Essential Oils Extracted from Aromatic Plants - Yahaya, Muhammad F.; Yelwa, Jibrin M.; Abdullahi, Shuaibu; Umar, Jamilu B.; Abubakar, Aliyu M.; Babakura, Mohammed (European Scientific Journal, ESJ, 2019)
Essential oils are substances obtained from plant materials and are complex mixtures whose composition varies. In this study, the chemical composition, and larvicidal activity of extracted essential oils from some aromatic plants were evaluated. Modified steam distillation apparatus was used to extract essential oils from the Citrus limon linn leaf, Vitex trifolia seed and Cananga odorata. Furthermore, the plant materials were tested using FTIR, GC-MS, and larvicidal activity test. Citrus limon linn produced more amount of essential oil (1.4ml), Vitex trifola (0.7ml) and Cananga odorata (0.5ml) after 3hours ofsteam distillation. The result obtained from the infrared spectra indicates the functional groups of the compounds present in Citrus limon linn, Vitex trifolia and Cananga odorata. GC-MS analysis identified, 13, 12 and 24 chemical constituents present in Citrus limon linn , Vitex trifolia and Cananga odorata essential oil respectively. The three main essential oil and their percentage compositions are D-Limonene (22.82%), Citral (25.20 %), and Cis-Verbenol (20.43%) for Citrus limon linn. Leaf essential oil, Sabinene (39.14%), Caryophyllene (26.45%) and 1 R- Î± Pinene (15.20%) for Vitex trifolia seed essential oil, and Linalool (35.30%), Ascabiol (23.54%), Caryophyllene (20.30%), Copaene (12.76%) and Germacrene D (11.32%). However, the results from the larvicidal activity reveals that essential oil extracted from Citrus limon linn, Vitex trifolia and Cananaga odorata may serve as insecticide and can be used as potent insecticide for the control of mosquitoes.